2006
DOI: 10.1002/bit.20959
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on enzyme preparations and role of cell components for (R)‐phenylacetylcarbinol production in a two‐phase biotransformation

Abstract: Whole cell pyruvate decarboxylase (PDC) from Candida utilis enhanced the enzymatic production of (R)-phenylacetylcarbinol (PAC) in an aqueous/octanol biotransformation compared to the partially purified PDC especially for a lower range of initial activities (0.3-2.5 U/mL). With an initial activity of 1.1 U/mL and at a 1:1 phase volume ratio, whole cell PDC achieved a maximum specific PAC production of 42 mg/U (2.8 g/L/h) in comparison to 13 mg/U (0.9 g/L/h) for partially purified PDC. The enhanced performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Use of the whole cells provided an extreme case of catalyst stabilization in the presence of 2-phenylpropanal: The isolated enzyme was deactivated by 0.5 mM aldehyde whereas the whole-cell catalyst and the supernatant thereof were able to tolerate and convert 1 M of the substrate. Stabilization of the catalytic enzyme by whole-cells and cell debris was previously reported for the synthesis of (R)phenylacetylcarbinol from benzaldehyde and pyruvate by a Candida utilis pyruvate decarboxylase (35). The stabilization was ascribed to membrane components that form a microenvironment around the enzyme and thereby decrease aldehyde transfer to the enzyme and protect the enzyme from deactivation at the aqueous/organic interphase.…”
Section: Catalyst Stabilizationmentioning
confidence: 87%
See 1 more Smart Citation
“…Use of the whole cells provided an extreme case of catalyst stabilization in the presence of 2-phenylpropanal: The isolated enzyme was deactivated by 0.5 mM aldehyde whereas the whole-cell catalyst and the supernatant thereof were able to tolerate and convert 1 M of the substrate. Stabilization of the catalytic enzyme by whole-cells and cell debris was previously reported for the synthesis of (R)phenylacetylcarbinol from benzaldehyde and pyruvate by a Candida utilis pyruvate decarboxylase (35). The stabilization was ascribed to membrane components that form a microenvironment around the enzyme and thereby decrease aldehyde transfer to the enzyme and protect the enzyme from deactivation at the aqueous/organic interphase.…”
Section: Catalyst Stabilizationmentioning
confidence: 87%
“…phenylacetylcarbinol from benzaldehyde and pyruvate by a Candida utilis pyruvate decarboxylase (35). The stabilization was ascribed to membrane components that form a microenvironment around the enzyme and thereby decrease aldehyde transfer to the enzyme and protect the enzyme from deactivation at the aqueous/organic interphase.…”
Section: Catalyst Stabilizationmentioning
confidence: 99%
“…The theory that the enzyme BAL is inactivated by the substrate 3,5-DMBA is in accordance with previous studies, in which an inactivation of a decarboxylase by benzaldehydes has also been reported. [16][17][18]…”
Section: Experimental Time Course Data and Competing Modeling Approachesmentioning
confidence: 99%
“…From a process perspective, the use of intact whole microbial cells that over-express specific recombinant ω -TAs may be advantageous, since it offers a more simple overall process configuration with a reduced number of upstream unit operations and less generation of waste material [9, 10]. Additionally, cell metabolism can be exploited for the (re)-generation of co-factors and co- substrates provided that there is an attendant assimilation of a carbon and energy source during the reaction [11].…”
Section: Introductionmentioning
confidence: 99%